Safety and outcomes of a structured exercise programme in young patients with hypertrophic cardiomyopathy: the SAFE-HCM trial. (25th November 2020) - Basu, J; Poveda Velazquez, P; Parry-Williams, G; Miles, C; Tilby-Jones, F; Sheikh, N; Malhotra, A; Bulleros, P; Chis Ster, I; O'Driscoll, J; Behr, E; Sharma, S; et al.
Abstract: Background: Contemporary studies in hypertrophic cardiomyopathy (HCM) suggest that moderate intensity exercise can improve cardiorespiratory fitness without raising significant safety concerns. Although low/moderate intensity exercise may be appropriate for older HCM patients, it is unlikely to attract younger, often asymptomatic patients, who wish to engage in higher intensity regimes. Purpose: To assess the feasibility, safety and outcomes of an individually tailored, high intensity exercise programme in young patients with HCM. Methods: In this RCT, 80 patients with HCM, aged 16–60 (mean 45.7, [SD8.6]) underwent baseline testing with ECG, echocardiography, blood testing, exercise testing, 48-hour ECG and psychological assessment. Individuals were randomised to a 12-week supervised exercise programme (HRR increased from 70–85%) (n=40) or usual activity (n=40). Baseline investigations were repeated at 12 weeks. Feasibility was assessed by a) recruitment, adherence and retention rates; b) staffing ratios and logistics; c) acceptability of the intervention/educational materials. Safety was assessed as a composite of 1) cardiovascular death, 2) cardiac arrest, 3) device therapy, 4) exercise induced syncope, 5) sustained/non-sustained (NS) ventricular tachycardia (VT) or 6) sustained atrial arrhythmias. Secondary outcomes included health and psychological benefits. Results: 67 individuals (82.5%) completed the study. Reasons for refusal included travel, work and family commitments. The majority (64.7%) of exercising individuals progressed to 85%HRR. Resource requirements were similar to other programmes. All individuals felt supported, more confident to exercise, and found educational materials clear and informative. There was no significant difference between groups for the composite safety outcome. One individual experienced exercise induced syncope due to ventricular standstill (exercise) and another sustained VT (control). Both required device implantation. There was no significant difference between groups in episodes of NSVT (p=0.573) or ectopic burden (p=0.729). At 12 weeks, exercise group participants demonstrated greater activity levels (+1.1 hours [CI 0.2–2.1], p=0.024). The change in peak aerobic capacity (+255.2ml/min [CI 93.2–417.1], p=0.003), time to anaerobic threshold (AT) (+115s [CI 54.2–176.0], p<0.001), total exercise time (+108.1s [CI 33.1–183.0], p=0.005) and oxygen uptake at AT (+2.44ml/kg/min [CI 0.6–4.2], p=0.009) were all significantly greater in the exercise group. HADS anxiety (p<0.001) and depression (p=0.017) scores demonstrated the greatest reduction in the exercise group. Conclusions: A high intensity exercise programme is feasible in young patients with HCM, with considerable gains in cardiorespiratory fitness and psychological outcomes. Importantly, arrhythmia burden was not increased in the exercise group. Further research is still required to assess the long-term safety of high intensity exercise in the HCM population. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): Cardiac Risk in the Young